Study of Black Rice Parents Performance and the Crossing Ability - Nandariyah, Nandariyah; Sukaya, Sukaya; Purnomo, Djoko; Sutarno, Sutarno; Yuniastuti, Endang; Az-Zahra, Catalina Dara Ayu (Universitas Sebelas Maret, 2023)
Black rice generally has problems in cultivation such as relatively long plant life, high habitus and low productivity. Plant breeders use several methods in hybridization activities, such as backcross method that can lead to the development towards emphasizing the superiority of each parent. This research aimed to study and determined the success rate of the black rice lines F1 backcross and the parents’ performance. This research was conducted using F1 of promising lines, parental lines and the Jeliteng variety with 9 sets of crosses. Each line and variety were repeated 3 times, in total there were 57 experimental units. The observation parameters of this research were plant height, crossing success, weight of seeds, length and width of grain, flowering age, harvesting age also number of grains and unfilled spikelet. The results of this study showed that parents plant height was positively correlated with the number of productive tillers. The taller the plant, the more productive tillers and the more flowers can be crossed. The success of the cross can increase with the number of flowers crossed. The success of crosses between F1 black rice promising lines and their parents has a success rate range of 10.82% to 33.75%. The findings imply that F1 crossbreeding of black rice promising lines with their parents can be carried out to produce backcross offspring.